HIV-1 activates oxidative phosphorylation in infected CD4 T cells in a human tonsil explant model - Freeman, Tracey L.; Zhao, Connie; Schrode, Nadine; Fortune, Trinisia; Shroff, Sanjana; Tweel, Benjamin; Beaumont, Kristin G.; Swartz, Talia H. (Frontiers in Immunology, 2023)
Human immunodeficiency virus type 1 (HIV-1) leads to a chronic, incurable infection that causes immune activation, resulting in chronic inflammation in people with HIV-1 (PWH) despite virologic suppression on antiretroviral therapy (ART). The mechanisms underlying this chronic inflammation are multifactorial; literature supports the role of lymphoid structures as reservoirs for viral latency and immune activation. The cell type-specific transcriptomic changes induced by HIV-1 infection in lymphoid tissue have not been analyzed. Human tonsil explants from four donors were infected with HIV-1 ex vivo. Single-cell RNA sequencing (scRNA-seq) was performed to evaluate the represented cell types and the impact of infection, differential gene expression, and inflammatory signaling pathways. Infected CD4+ T cells exhibited increased respiratory electron transport pathway genes, activating oxidative phosphorylation. Additionally, macrophages exposed to the virus but uninfected demonstrated increased NLRP3 inflammasome pathway genes, activating the NLRP3 inflammasome and stimulating proinflammatory signaling pathways and pyroptotic cell death. These observations support important mechanistic understanding to drive the development of therapeutic strategies to eradicate disease in PWH.